ANALISIS PEMAHAMAN MAHASISWA UNIVERSITAS NEGERI MEDAN TERHADAP KONSEP SIFAT KOLIGATIF LARUTAN DALAM PEMBELAJARAN KIMIA - Serli Nawati Azhari; Syafitri, Amelia (Journal of Research and Education Chemistry, 2025)
This study aims to analyze students' understanding of the concept of colligative properties of solutions in chemistry learning. The research method used is a quantitative method with data collection techniques through a dare questionnaire distributed using Google Form. The research subjects consisted of students of Medan State University who had studied the topic of colligative properties of solutions. The questionnaire used contained a series of closed and open questions to measure the level of students' understanding, including conceptual aspects, applications in daily life, and difficulties faced in understanding the material. The data obtained were analyzed statistically using descriptive tests to determine the distribution of students' understanding, as well as correlation tests to see the relationship between certain factors, such as academic background and learning resources used. The results showed that the level of students' understanding varied, with most students having a moderate understanding of the concept of colligative properties of solutions. Factors that contributed to this level of understanding included the teaching method used, the availability of learning resources, and students' learning motivation. The main challenge faced by students was in understanding the concepts of osmotic pressure and freezing point depression. These findings have an impact on improving chemistry learning strategies, especially in the use of more interactive and contextual methods to help students understand the concept of colligative properties of solutions more deeply.